A Contrastive Analysis Of Consonant Sounds In English And Indonesian “Anti-Hero” Song - Josua Menanti Wind Lumban Tungkup; Mika Dwi Paskaria Ambarita; Desmantha Purba; Anita Sitanggang (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The phonetic systems of English and Indonesian are compared and contrasted in the lyrics of the song "Anti-Hero." The research intends to compare and contrast the phonemes in song lyrics in order to teach students how to pronounce English using Indonesian phonemes. This research focuses on 15 English consonant phonemes and 15 Indonesian consonant phonemes. The descriptive-contextual research methodology employs a qualitative technique. The technique compares phonemes in song lyrics written in English and Indonesian based on the sorts of phonemes. The "Anti-Hero" song lyrics, which are made up of 15 consonant phonemes, were revealed to have similarities between the English and Indonesian phonemic systems. The disparities are represented by 15 consonants in the song "Anti-Hero" lyrics.